Anodic Polarization of Anodized Aluminum Alloy 5052 - S. Yaro, Aparel; Mishgel Ali AL-Asade, Ala’a (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Aluminum alloy 5052 had been anodized by sulfuric acid as an electrolyte under constant voltage and the anodic oxide film produce will be testing by potentiostatic anodic polarization .Two variables, which were considered as important variables, were studied. These variables are anodizing time 15,30 min. and sealing time 10,20 min., and the test by potentiostatic anodic polarization through electro chemical polarization measurements in solutions of 1N na2so4 ( PH= 1 ). The results are discussed in light of the rate of ionic current flow through the coating during anodic polarization measurements.